Comprehensive polyphenolic profiling in promising resistant grapevine hybrids including 17 novel breeds in northern Italy. (26th October 2020) - Gratl, Verena; Sturm, Sonja; Zini, Elena; Letschka, Thomas; Stefanini, Marco; Vezzulli, Silvia; Stuppner, Hermann
Abstract: BACKGROUND: A promising way to overcome the susceptibility of Vitis vinifera L. to fungal diseases is the integration of genetic resistance by the interspecific crossing between V. vinifera varieties and resistant species. However, the products of such hybrids are still not accepted by customers, particularly due to their organoleptic characteristics, not least influenced by their polyphenolic profile. RESULTS: A total of 58 resistant breeding lines, 41 from international programs and 17 new progeny individuals, were grown in one untreated vineyard to exclude any variances by climatic and pedologic conditions or vineyard practice. A total of 60 polyphenols (including acids, anthocyanins, flavonols, flavan‐3‐ols, and stilbenoids) were determined in grapevine berries by ultrahigh‐performance liquid chromatography–mass spectrometry in two consecutive years. The overall profiles were rather consistent (variation P  > 0.05) within the two harvests, with the exceptions of epicatechin and caftaric acid. Anthocyanin diglucosides were found in ten of the red breeding lines, malvidin‐3, 5‐ O ‐diglucoside being predominant in nine of them. Total polyphenol content of the unknown progeny individuals and international breeding lines was comparable, with the exception of significantly increased amounts of gallic acid and some flavonoids. CONCLUSION: The comprehensive study reported herein of the polyphenolic profile of hybrids from international breeding programs, but also of new breeds from private initiatives, all cultivated in the same vineyard, will support the selection of promising candidates for further breeding programs to overcome impairment due to undesired sensory characteristics of new highly resistant varieties.